Wearable-based electronics to objectively support diagnosis of motor impairments in school-aged children. (23rd January 2019) - Ricci, Mariachiara; Terribili, Monica; Giannini, Franco; Errico, Vito; Pallotti, Antonio; Galasso, Cinzia; Tomasello, Laura; Sias, Silvia; Saggio, Giovanni
Abstract: Developmental coordination disorder (DCD) and attention-deficit hyperactivity disorder (ADHD) are neuro-developmental disorders, starting in childhood, which can affect the planning of movements and the coordination. We investigated how and in which measure a system based on wearable inertial measurement units (IMUs) can provide an objective support to the diagnosis of motor impairments in school-aged children. The IMUs measured linear and rotational movements of 37 schoolchildren, 7−10yo, 17 patients and 20 control subjects, during the execution of motor exercises, performed under medical and psychiatric supervision, to assess different aspects of the motor coordination. The measured motor parameters showed a high degree of significance in discriminating the ADHD/DCD patients from the healthy subjects, pointing out which motor tasks are worth focusing on. So, medical doctors have a novel key lecture to state a diagnosis, gaining in objectivity with respect to the standard procedures which mainly involve subjective human judgment. Differently to other works, we propose a novel approach in terms of number of used IMUs and of performed motor tasks. Moreover, we demonstrate the meaningful parameters to be considered as more discriminant in supporting the medical diagnosis.